Benefit Incidence Analysis of Public Spending on Education in the Philippines: A Methodological Note - Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2008)
Benefit incidence analysis (BIA) is a tool used to assess how tax policy or government subsidy affects the distribution of welfare in the population. In other words, it evaluates the distribution of government subsidies among different groups in the population, in particular, among different income groups. The methodology involved in benefit incidence approach is straightforward. Nevertheless, defining deciles (or quintiles) is critical as benefit incidence estimates depend heavily on the number of individuals occupying each decile (or quintile) cell. Deciles can be defined over population, i.e., across individuals and across households. The purpose of this methodological note is to briefly illustrate the difference in benefit incidence estimates that are obtained when deciles of population/individuals in lieu of deciles of households are used in the analysis as applied on government spending on education in the Philippines.
Keywords: 330; targeting; education; benefit incidence analysis; Gini coefficient; concentration coefficient; concentration curve; progressivity; Bildungsniveau; Bildungsfinanzierung; Gini-Koeffizient; Theorie; Philippinen